(untitled) (Nuntius Antiquus, 2010)
This article deals with different manifestations of violence, including the distortions and mistakes that maternal or other kind of love can produce on the object of its affections. In order to reflect about this theme, we focus on some ancients sources, such as Plutarch’s Of the affection towards offspring, mythological narratives and excerpts of Greek tragedies. To understand some aspects of the dynamics of good and evil, we recur to the thought of the French philosopher Paul Ricoeur.